Implementing the SDGs in local contexts: overcoming methodological boundaries (Revista Nacional de Administración, 2021)
The research suggests how the full potential of the enterprises and organizations of the Social and Solidarity Economy in promoting sustainable development may be better understood by representing cultural, social, economic, and environmental issues within an integrated analytical framework. On these premises, an extended version of Coraggio’s scheme (2015) is obtained by adding a fourth sector of economic activity, namely the global economy, as opposed to the popular economy. Looking at Coraggio’s integrated scheme, an additional institutional space related to the social and solidarity economy emerges, representing the field of digital solidarity and cooperation. Then, the research helps to clarify what a local context is and how it relates to the notion of place. Finally, the notion of place is contrasted with the notion of system, as the attractiveness of the former depends on its distinctive features, while the latter emphasizes the instrumental value of its elements.